MODEL APPLICATION TYPE COOPERATIVE LEARNING STAD (STUDENT TEAM DIVISION ACHIVEMENT) TO IMPROVE STUDENT LEARNING CLASS RESULTS IV.A SDN 091 PEKANBARU - Deka Tria Febriana Deka Tria Febriana; Gustimal Witri Gustimal Witri; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was motivated by the low learning outcomes Mathematics fourth grade students of SDN 91 Pekanbaru. Drinking completeness criteria (KKM) has yet to reach the target. Where the daily test students who reach the target KKM only 31.25% (10 people), and which does not achieve as much KKM 68.75% (22) of 32 students. This study is a Class Action Research (CAR), which aimed to improve student learning outcomes Math class IV.A SD 91 Pekanbaru. Formulation of the problem: Is cooperative learning model (STAD) can improve mathematics learning outcomes fourth grade students of SDN 91 Pekanbaru. The research was conducted on March 17, through April 3, 2014. The subjects were fourth grade students of SDN 91 Pekanbaru, amounting to 32 students as a source of data. Instrument data collection in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the study results obtained from the value of the daily tests before treatment with 31.25%. Increased in the first cycle to 76.75 or 24.79% increase .In the second cycle increased to 82.31 or 58.37% increase. In the third cycle increased to 82.71 or 59.14% increase. Activity of teachers in the learning process in the first cycle and the first meeting 59.38% or 68.75% second meeting. Cycle II first meeting of 71.86%, 78.12% .And the second meeting of the third cycle of the first meeting of the second meeting of 87.5% to 100%. The results of the study in class IV SDN 91 Pekanbaru prove that the implementation of cooperative learning model Student Teams Achievement Division (STAD) can improve learning outcomes Mathematics fourth grade students of SDN 91 Pekanbaru. Keywords : Cooperative Learning Model STAD, Mathematics Learning Outcomes